Knowledge, attitude, and practice of dental practitioners toward the medicolegal system: A cross-sectional questionnaire study - Ruchika Kallianpur; Treville Pereira; Subraj Shetty; Swati Gotmare; Christina Pereira; A K Anjali (Wolters Kluwer Medknow Publications, 2022)
Background: Every element of human involvement is affected by the law, and dentistry is no exception in this respect. The efficient implementation and development of comprehensive care is halted by a lack of awareness of the medicolegal aspects. Awareness of the medicolegal system is as essential as professional competence in the practice of medicine. It only makes it vital for health practitioners to be informed of medical law and ethics because of heightened understanding among patients about the same. Aim: The aim of this study was to evaluate the knowledge and awareness on medicolegal issues among dental practitioners in Mumbai. Materials and Methods: A self-structured, pretested, close-ended, self-administered questionnaire was conducted on 100 dental graduates and postgraduates across Mumbai compromising 11 questions related to the medicolegal system, Consumer Protection Act, and informed consent. Conclusion: Participants were aware of the various aspects of the medical legal system, but lacked comprehension of the finer points. However, they lacked basic information in regard to the medicolegal programs and courses offered in the country.